Plan de riesgos crediticios de la cooperativa de ahorro y crédito 9 de Octubre ltda., del periodo académico del 01 de enero al 31 de diciembre del 2013 - Chiliquinga Toapanta, Ana Maricela (2015)
This research is focused on credit risk management of the cooperative, in order to improve portfolio expired within the institution, through the identifying, measurement, control and monitoring of these risks, with the purpose of prevent and maintain a level of adequate patrimony provisions and equity are considered desirable first discuss issues on how to distinguish the purpose of this investigation. (descriptive, analytical, systematic) and technical observation, survey methods was used for this purpose, several instruments for collecting data from primary sources, such as interviews and surveys, development, implementation of questionnaires, administrative staff were implemented of the cooperative, let to study the feasibility of providing useful and relevant information on the current situation of the company, which could be obtained as a result that should have a Plan Credit Risk on the model of credit scoring, allowing mitigate it within the organization….